The impact of external control on the rationalization of spending in government institutions at Karak Governorate, Jordan - Aldmour, Faris Awad (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to measure the impact of external control on the rationalization of spending in government institutions in the Karak governorate from the point of view of its employees. To achieve the objectives of the study, a questionnaire was used as a main tool for data collection, and it was distributed to a randomly selected sample of (360) employees. Total of (330) valid questionnaires were returned for statistical analysis, at a rate of (91.6%) of the total distributed questionnaires. After analyzing the data, the study reached a set of results, the most important of which are: that the level of application of external control in government institutions in Karak governorate came to a high degree, and that the arithmetic averages of respondents’ perceptions of the level of rationalization of spending in government institutions in Karak governorate came at a high level at the total level, and that there are A statistically significant effect at the significance level (α ≥ 0.05) of external control on the rationalization of spending in government institutions. In light of the results reached, the study recommended the need for government institutions in the Karak governorate to improve and develop ways to rationalize spending; this is because of its great importance in helping government institutions to face the challenges that stand in the way of achieving their goals and preserving public funds from loss.